Modelling the Impact of Environmental Regulations on Bilateral Trade Flows: OECD, 1990-1996 - Harris, Mark; Kónya, L.; Mátyás, L. (Wiley-Blackwell Publishing, 2002)
Since the early seventies policy makers and academics alike have been paying increasing attention to the interaction between environmental regulation and foreign trade. The theories and methodologies applicable to this diverse and complex relationship are surveyed among others by Anderson and Blackhurst (1992), Dean (1992), Van Beers and Van den Bergh (1996) and Xing and Kolstad (1996). The specific issues investigated are numerous, ranging from the environmental determinants of trade, through the impact of trade on the environment and the effects of environmental policy on trade, to the substitution or complementarity of trade and environmental policy measures. The focus of this paper is on the relationship between the relative stringency of environmental regulations and international competitiveness. A three-dimensional panel data framework is employed, which allows for both importing and exporting country effects, as well as for time (or business cycle) effects. Even if these additional specific effects are insignificant, the panel data set used is expected to be more reliable and enlightening than a simple cross-sectional data set, since bilateral trade, especially on the lower, two- and three-digit SITC levels, is often prone to strong annual fluctuations. As the analysis shows, as soon as these specific effects are taken into consideration, the relationship between stricter regulations and foreign trade becomes statistically insignificant. This suggests that environmental costs do not have a real impact, either negative or positive, on foreign trade. The paper is structured as follows. The model is briefly described in Section 2. Section 3 discusses the measurements and sources of the data used, with special regard to the strictness of environmental regulations. The empirical findings are summarized in Section 4. Finally, the concluding remarks can be found in Section 5.